A Note on Boolean Like Algebras - Pushpalatha, K.; M.L.Hima Bindu, V. (International Journal of Engineering and Technology, 2018)
In this paper we develop on abstract system: viz Boolean-like algebra and prove that every Boolean  algebra is a Boolean-like algebra.  A necessary and sufficient condition for a Boolean-like algebra to be a Boolean algebra has been obtained.  As in the case of Boolean ring  and Boolean algebra, it is established that under suitable binary operations the Boolean-like ring and Boolean-like algebra are equivalent abstract structures.